2013
DOI: 10.1159/000346815
|View full text |Cite
|
Sign up to set email alerts
|

Urine Catalytic Iron and Neutrophil Gelatinase-Associated Lipocalin as Companion Early Markers of Acute Kidney Injury after Cardiac Surgery: A Prospective Pilot Study

Abstract: Background: Open heart surgery with cardiopulmonary bypass is recognized as a common cause of acute kidney injury (AKI). The conventional biomarker creatinine is not sensitive enough to detect AKI until a significant decline in renal filtration has occurred. Urine neutrophil gelatinase-associated lipocalin (NGAL), part of an acute response to the release of tissue iron from cells, is an early biomarker and a predictor of AKI in a variety of clinical settings. We sought to evaluate the relationship between urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 88 publications
0
20
2
Order By: Relevance
“…However, iron is excreted mainly through sloughed mucosal cells in the gastrointestinal tract rather than in the urine. In addition, urinary catalytic iron levels are increased, not decreased, in patients with AKI (29). Finally, we found no correlation between eGFR and plasma catalytic iron levels.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, iron is excreted mainly through sloughed mucosal cells in the gastrointestinal tract rather than in the urine. In addition, urinary catalytic iron levels are increased, not decreased, in patients with AKI (29). Finally, we found no correlation between eGFR and plasma catalytic iron levels.…”
Section: Discussioncontrasting
confidence: 70%
“…In a pilot study of 14 patients undergoing cardiac surgery, urinary catalytic iron levels increased significantly within 8 hours in patients who developed AKI (29). In a larger study (n=806), plasma catalytic iron levels measured 24 hours after radiocontrast administration were higher among patients with versus without established contrast nephropathy (15).…”
Section: Discussionmentioning
confidence: 91%
“…Further studies, however, are required to investigate whether other mechanisms may supersede Lcn2 to induce/maintain hypoferremia during the later phase of chronic colitis. Although our study did not detect significant correlation between urinary CI and Lcn2, one study reported a positive correlation in patients with high risk in developing acute kidney injury after undergoing open heart surgery (Akrawinthawong et al 2013). Such discrepancy could be due to the differences in (1) the model or pathological condition (murine vs human), (2) the time points in which samples were collected, (3) type of tissue analyzed, and (4) use of any medication.…”
Section: Discussioncontrasting
confidence: 94%
“…In CKD patients undergoing elective coronary angiography with contrast, postprocedural NGAL increases from baseline in each stage of CKD [46] . In patients undergoing open heart surgery with AKI, urine catalytic iron levels are highly correlated with urine NGAL levels [47] . The difference in AUROC values of NGAL between SHRs and humans may be due to the young age of SHRs (5 months old) in an animal model used by Rouse et al [6]; therefore, the level of NGAL may not yet reflect severely worsening AKI.…”
Section: Similar Pathogenesis Of Ed and Asymmetric Dimethylarginine Imentioning
confidence: 99%